Infrastructure Development and Food Security in Indonesia: The Impact of the Trans-Java Toll Road on Rice Paddy Farmersâ Desire to Sell Farmland - Yogi Makbul; Uly Faoziyah; Sudrajati Ratnaningtyas; Benedictus Kombaitan (The Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
This paper addresses the implications of infrastructure development for regional food security. The development of the Trans-Java toll road threatens food security in Indonesia, especially in the northern part of Java, the largest producer of rice paddy in the country. This development can raise land prices near the toll road, particularly near the toll gates, which tends to encourage farmers to sell their farmland. Thus, farmland will likely be converted to non-agricultural uses. The farmersâ decisions have a major influence on food security, related not only to a decline in productive agricultural land area but also related to the ability of the region to supply rice to other parts of the country. This research analyzed the characteristics of rice paddy farmers who desire to sell their farmland. Using the Mann-Whitney U test statistical technique this research focused on Gantar District, the highest paddy producing district in Indramayu Regency, which is passed by the Trans-Java toll road. The respondents were farmers who were members of farmersâ groups in the area; the sample was selected using random cluster sampling. The results show that farmers who desire to sell their farmland are those who can get a high price for their farmland, have low income, and are less active in farmersâ groups. From these results, we suggest that the government should more actively implement programs to make farmersâ groups more attractive in order to ensure that the members will be more active, thereby facilitating the promotion of the importance of food security in Indonesia. Abstrak. Makalah ini membahas implikasi pembangunan infrastruktur untuk ketahanan pangan regional. Perkembangan jalan tol Trans-Jawa mengancam ketahanan pangan di Indonesia, terutama lahan sawah di Jawa utara yang merupakan penghasil padi terbesar di Indonesia. Ini dapat menaikkan harga tanah di dekat jalan, terutama di dekat gerbang tol dan cenderung mendorong petani untuk menjual tanah pertanian mereka, sehingga kemungkinan akan mengubah lahan pertanian menjadi kegiatan non-pertanian. Keputusan petani ini memiliki pengaruh besar pada ketahanan pangan, terkait tidak hanya dengan penurunan lahan pertanian produktif, tetapi juga pada kemampuan daerah untuk memasok beras ke daerah lain. Oleh karena itu, penelitian ini dimaksudkan untuk menganalisis karakteristik petani padi yang ingin menjual tanah pertanian mereka. Dengan menggunakan teknik statistik uji Mann-Whitney U, penelitian ini berfokus pada Kabupaten Gantar, kabupaten penghasil padi tertinggi di Kabupaten Indramayu yang dilewati oleh jalan tol Trans-Jawa. Responden adalah petani yang merupakan anggota kelompok petani di daerah tersebut, dan sampel dipilih menggunakan cluster random sampling. Hasilnya menunjukkan bahwa petani yang ingin menjual tanah pertanian mereka adalah mereka yang dapat mendapatkan harga tinggi untuk tanah pertanian mereka, berpenghasilan rendah, dan kurang aktif dalam kelompok tani. Dari hasil ini, kami menyarankan bahwa pemerintah harus lebih aktif mengimplementasikan program untuk membuat aktivitas kelompok petani lebih menarik untuk memastikan bahwa anggota akan lebih aktif, sehingga memfasilitasi promosi pentingnya ketahanan pangan di Indonesia. Kata kunci. Jalan tol Trans-Jawa, konversi lahan pertanian, ketahanan pangan, Indonesia, sawah.